Service Quality Factors Affecting Customer Satisfaction at the Registration Office, Bang Rachan District, Sing Buri Province: Service Quality Factors Affecting Customer Satisfaction at the Registration Office, Bang Rachan District, Sing Buri Province - Meuanchan, Neramit; Kenaphum, Sanya; Kosonkittiumporn, Saovalak (RATANABUTH JOURNAL, 2025)
The research objectives of this study were 1) study the satisfaction level of service recipients of the Bang Rachan District Registration Office, Sing Buri Province; 2) study the service quality factors affecting the satisfaction of service recipients of the Bang Rachan District Registration Office, Sing Buri Province; and 3) study the guidelines for developing the service quality of service recipients of the Bang Rachan District Registration Office, Sing Buri Province. The sample group consisted of 325 people who came to receive services from the Bang Rachan District Registration Office, Sing Buri Province, using Taro Yamane's formula. The research instruments used were a rating scale questionnaire and an in-depth interview. The target group consisted of 10 officers and service recipients. The statistics used for data analysis were percentage, mean, frequency, standard deviation, linear multiple regression analysis, and content analysis. The research results indicated 1) the overall satisfaction level of service recipients of the Bang Rachan District Registration Office, Sing Buri Province was at a high level. 2) The service quality factors affecting the satisfaction of service recipients of the Bang Rachan District Registration Office, Sing Buri Province, namely, reliability, customer responsiveness, and tangibility of services, could significantly predict the satisfaction of service recipients of the Bang Rachan District Registration Office, Sing Buri Province by 77.20 percent. At the .05 statistical level and 3) Suggestions for development include improving the environment, arranging the place to be clean and tidy, having clear signs, adding waiting seats and areas to support vulnerable groups, using online queue booking technology, enhancing credibility, setting transparent service standards, training staff to have knowledge of the law and service procedures, and providing a feedback system, developing customer response, adding more contact channels, reducing waiting time with a queue booking system and express service, training staff in communication skills, building confidence among service recipients, developing staff skills, displaying service information transparently, and improving the data security system, understanding the needs of the public, studying the characteristics of service recipients, reducing complicated steps, and developing a feedback system.